The Closer the Better? Modeling Spatial Spillover Effects of Ecological Externalities in Coastal Mangroves - Wang, Han; Zheng, Qiwen; Li, Shuang; Yang, Xiaoyu (Frontiers in Marine Science, 2021)
TAs an important part of ecological externalities, spatial spillover effect has attracted the attention of environmental economics researchers. However, the traditional view that the spillover mechanism of ecological externalities generally decreases with the increase of distance remains to be improved. In order to innovate the spatial distribution calculation method of the externality spillover mechanism of ecological protection zones and optimize the current ecological compensation policy, this study takes the wetland protection zone in Beihai City, Guangxi Province, China as an example, attempts to introduce the concept of geographical accessibility and the two-step mobile search (2SFCA) model, and uses the distance factor to combine the ecosystem with the individual characteristics of farmers and visualize them, so as to measure the mechanism of the ecological externality spillover mechanism of wetland protection zones. However, this study found that the change of ecological externality spillover mechanism in the ecological reserve is not only affected by ecosystem service value and spatial distance, but also by the individual characteristics of residents around the region, including residents ' cognition of the function of the ecological reserve, residents ' livelihood types, the number of behaviors to the reserve, and the willingness to protect the ecological environment, which will also lead to spatial changes in the intensity of wetland ecological externality spillover. Residents who rely on the nature reserve to provide derivative products to maintain livelihoods, have high geographical accessibility and strong willingness to protect show stronger spatial spillover effects. The conclusion of this study is helpful for managers to rationally develop and utilize ecosystems according to the specific situation of different residents, and put forward more reasonable protection policies to realize the sustainable development of man and nature.